USING OF DISTANCE LEARNING TECHNOLOGIES TO CONTROL OF INDEPENDENT STUDENTS WORK IN THE STUDY OF HISTOLOGY - Barinov, E.F.; Nikolenko, O.I.; Tereshchuk, B.P.; Krahotkina, E.D.; Cherkasova, N.A. (World of Medicine and Biology, 2015)
To summarize the experience of using distance learning technologies (DLT) at the histology, cytology and embryology department of the Donetsk National Medical University, to evaluate the effectiveness and to make recommendations on the structure and content of the didactical materials for the management of independent work of students. Methods: analysis of practice of student’s independent work organization. The DLT are based on software product LMS MOODLE and include aimed, methodical, training, advising and monitoring units. Results: Using DLT the structure of student’s workload has changed (80,7% of students became engaged on 3-4 hours in preparation for the practical classes). According to the results of the test monitoring an increase was marked in quality progress, which reflects the effectiveness of student’s independent work from 40,6% ± 7,3% up to 62,5% ± 5,0% (p = 0,045). Conclusions: The use of DLT on e-learning platform Moodle enables optimal organization and thus it increases the efficiency of independent work of students in preparation for histology practical classes.